Dampak Penggunaan Gadget terhadap Minat Belajar Anak Usia Dini dan terhadap Lingkungan Sekitar - Olifia Widi Anggrahini; Kanya Indah Fanisa; Baeti Rahmawati; Meivia Nur Damayanti (Jurnal Pelayanan Masyarakat, 2024)
The use of gadgets among young children is increasing along with the development of technology. Gadgets have the potential to be a fun and useful learning tool if used appropriately. However, excessive use of gadgets has a negative impact, children who spend too much time with gadgets tend to lose interest in learning, such as reading books or participating in educational games. Additionally, their social interactions with peers and family may also be disrupted, ultimately affecting their social and emotional development. Student service to the community regarding the impact of gadget use on early childhood learning interest and the environment. It is carried out in one stage, namely the stage of providing material which aims to provide an understanding of how to use gadgets wisely so that they can still learn effectively while maintaining a balance with other activities that support their growth and development.